Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

The function [tex]\( f(x) = x + 15 \)[/tex] is one-to-one.

a. Find an equation for [tex]\( f^{-1}(x) \)[/tex], the inverse function.

b. Verify that your equation is correct by showing that [tex]\( f(f^{-1}(x)) = x \)[/tex] and [tex]\( f^{-1}(f(x)) = x \)[/tex].

c. Select the correct choice below and fill in the answer box(es) to complete your choice.
(Simplify your answer. Use integers or fractions for any numbers in the expression.)

A. [tex]\( f^{-1}(x) = \square \)[/tex], for [tex]\( x \neq \square \)[/tex]

B. [tex]\( f^{-1}(x) = \square \)[/tex], for [tex]\( x \geq \square \)[/tex]

C. [tex]\( f^{-1}(x) = \square \)[/tex], for [tex]\( x \leq \square \)[/tex]

D. [tex]\( f^{-1}(x) = \square \)[/tex], for all [tex]\( x \)[/tex]


Sagot :

Let's solve the given question step-by-step.

### Part (a): Finding the Inverse Function

We are given the function:
[tex]\[ f(x) = x + 15 \][/tex]

To find the inverse function [tex]\( f^{-1}(x) \)[/tex], we need to follow these steps:
1. Replace [tex]\( f(x) \)[/tex] with [tex]\( y \)[/tex]:
[tex]\[ y = x + 15 \][/tex]

2. Swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex] to find the inverse equation:
[tex]\[ x = y + 15 \][/tex]

3. Solve for [tex]\( y \)[/tex]:
[tex]\[ y = x - 15 \][/tex]

So, the inverse function [tex]\( f^{-1}(x) \)[/tex] is:
[tex]\[ f^{-1}(x) = x - 15 \][/tex]

Therefore, the correct choice is:
[tex]\[ D. \; f^{-1}(x) = x - 15 \; \text{for all } x \][/tex]

### Part (b): Verifying the Inverse Function

We will now verify that the inverse function [tex]\( f^{-1}(x) = x - 15 \)[/tex] is correct by showing that:
1. [tex]\( f(f^{-1}(x)) = x \)[/tex]
2. [tex]\( f^{-1}(f(x)) = x \)[/tex]

1. Verification of [tex]\( f(f^{-1}(x)) = x \)[/tex]:
- Substitute [tex]\( f^{-1}(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(f^{-1}(x)) = f(x - 15) \][/tex]
- Apply the function [tex]\( f \)[/tex]:
[tex]\[ f(x - 15) = (x - 15) + 15 = x \][/tex]
Therefore,
[tex]\[ f(f^{-1}(x)) = x \][/tex]

2. Verification of [tex]\( f^{-1}(f(x)) = x \)[/tex]:
- Substitute [tex]\( f(x) \)[/tex] into [tex]\( f^{-1}(x) \)[/tex]:
[tex]\[ f^{-1}(f(x)) = f^{-1}(x + 15) \][/tex]
- Apply the inverse function [tex]\( f^{-1} \)[/tex]:
[tex]\[ f^{-1}(x + 15) = (x + 15) - 15 = x \][/tex]
Therefore,
[tex]\[ f^{-1}(f(x)) = x \][/tex]

### Conclusion
Since both verifications hold true, we have confirmed that the inverse function is indeed correct. Thus, the inverse function is:
[tex]\[ f^{-1}(x) = x - 15 \; \text{for all } x \][/tex]
And the correct choice is:
[tex]\[ D. \; f^{-1}(x) = x - 15 \; \text{for all } x \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.